A Workflow for Assessing Particle Counts of Mixed Micro- and Nanoplastics in Exposed Laboratory Animals - Lauren Gaspar; Sarah Davis; Giuseppe Coppotelli; Andrew J. Davies; Coleen C. Suckling; Jaime M. Ross (Nanomaterials)
Micro- and nanoplastics (NMPs) have recently gained attention as one of the most pervasive and potentially dangerous environmental pollutants. An increasing number of studies have explored the presence and potential health consequences of NMPs exposure, leading to calls for techniques to assess their bioaccumulation. Significant gaps that remain in this growing field of research are methodologies to quantify discrete particle counts of NMPs below 5 μm in size and evaluate the recovery rate of such methods to ensure accuracy and comparability across studies. To address these gaps, we aimed to develop a high-throughput protocol for the extraction, isolation, and quantification of a 1:1 volume mixture of 2 and 0.1 μm pristine fluorescently labeled spherical polystyrene NMPs (PS-NMPs) from mouse tissue, and to determine recovery rates of both sizes to assess the success of the methodology. We found that we were able to successfully recover 85% of 2 μm NMPs and 30% of 0.1 μm NMPs, and that this workflow could be applied to tissues from mice experimentally exposed to a concentration gradient of PS-NMPs to detect differences in accumulation. This methodology is the first to attempt a continuous workflow to assess particle counts of both micro- and nanoplastics from biological tissues, including calculations of recovery rates, and we anticipate that the workflow described here may be applied and modified in future studies to answer outstanding questions regarding the accumulation of small NMPs that may not be addressed with traditional techniques. Additionally, in identifying the significant differences in recovery rates for micro- versus nanoplastics, we highlight the considerations that must be taken into account for nanoplastics that are often not discussed within the NMPs literature.